Analisis Peramalan Produk Ayam Geprek Mister Cafe Kota Gunungsitoli (Lembaga Pengembangan Kinerja Dosen, 2025)
At Mister Café Gunungsitoli, the researcher found that employee service was slow in fulfilling customer requests for product orders at UD. Toko Sinar Terang Gunungsitoli. The purpose of this study is to determine the sales forecasting of Ayam Geprek at Mister Café Gunungsitoli for the years 2023 and 2024 using the Single Moving Average method with 3 periods and 5 periods, and to identify which forecasting method is most effective for predicting sales of Ayam Geprek at Mister Café Gunungsitoli. This study employs a quantitative research approach with data calculations using the Single Moving Average method to obtain accurate results. The findings indicate that sales of Ayam Geprek products at Mister Café Gunungsitoli during the period of January 2023 – December 2024 experienced fluctuations influenced by seasonal factors, consumer consumption trends, and promotional activities. These fluctuations highlight the importance of applying forecasting methods so that the company can adjust production capacity in line with consumer demand. The results of the comparative analysis of forecasting methods (Moving Average) show the smallest error rate, making it more appropriate to use MAPE with 5 periods, which yielded a value of 36.43%.